Pendekatan Qur’ani terhadap Krisis Lingkungan: Strategi Penanggulangan Sampah Plastik dan Polusi - Rawzalgina, Arthi Amalia; Titin Hurniati (Kartika: Jurnal Studi Keislaman, 2026)
The global environmental crisis, marked by increasing plastic waste and pollution, has become a serious threat to the sustainability of human life and other living creatures. International and national data show that air, water, and soil pollution continue to increase in line with exploitative and unsustainable human consumption patterns. This paper aims to examine the reality of the contemporary environmental crisis, identify verses in the Qur'an related to the environment, and formulate Qur'anic solutions to the problems of plastic waste and pollution. This study uses a qualitative-descriptive approach based on a literature review with a thematic interpretation (maudhu'i) method. The results of the study show that the Qur'an positions humans as caliphs on earth who bear the responsibility to maintain balance (mīzān) and prohibits all forms of destruction (fasād) and waste (isrāf). The ecological values contained in the Qur'an are an ethical and spiritual foundation that is relevant for responding to the modern environmental crisis. The Qur'anic solutions offered include strengthening eco-theological awareness, changing consumptive lifestyles towards environmentally friendly patterns, strengthening government regulations, and integrating environmental education based on Qur'anic values. Thus, the Qur'anic approach is not only normative but also applicable in efforts to preserve the environment in a sustainable manner.